Health facility delivery among women of reproductive age in Nigeria: Does age at first birth matter? - Obasanjo Afolabi Bolarinwa (Public Library of Science (PLoS), 2021)
Background High maternal mortality ratio in sub-Saharan Africa (SSA) has been linked to inadequate medical care for pregnant women due to limited health facility delivery utilization. Thus, this study, examined the association between age at first childbirth and health facility delivery among women of reproductive age in Nigeria. Methods The study used the most recent secondary dataset from Nigeria's Demographic and Health Survey (NDHS) conducted in 2018. Only women aged15-49 were considered for the study (N = 34,193). Bi-variate and multivariable logistic regression models were used to examine the association between age at first birth and place of delivery. The results were presented as crude odds ratios and adjusted odds ratios (aOR) with corresponding 95% confidence intervals (CIs). Statistical significance was set at p<0.05. Results The results showed that the prevalence of health facility deliveries was 41% in Nigeria. Women who had their first birth below age 20 [aOR = 0.82; 95%(CI = 0.74-0.90)] were less likely to give birth at health facilities compared to those who had their first birth at age 20 and above. Conclusion Our findings suggest the need to design interventions that will encourage women of reproductive age in Nigeria who are younger than 20 years to give birth in health facilities to avoid the risks of maternal complications associated with home delivery. Such interventions should include male involvement in antenatal care visits and the education of both partners and young women on the importance of health facility delivery.